Peningkatan Hasil Belajar Bahasa Indonesia Melalui Pendekatan TARL Model Pembelajaran Problem Based Learning pada Siswa Kelas 1 SDN Pakis V Surabaya - Ifa Ayiyida; Indira Fitria Aisyah; Rerika Landaini Putri; Desi Eka Pratiwi (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
The Merdeka Curriculum emphasizes individual freedom to learn according to their potential. Thus, teachers face the challenge of providing instruction that suits students' varying abilities. In addition, many students face difficulties in multiplication and division when studying mathematics. So, the aim of this research is to find out whether student learning outcomes are better by using the Problem Based Learning (PBL) model in learning Indonesian in one grade. Learning Indonesian in first grade often faces problems in improving students' skills. Consequently, the aim of this research is to apply the PBL learning model and learning approach at the appropriate level (TaRL) at SDN Pakis V Surabaya. The aim of this research is to explain the use of TaRL in Indonesian language learning in grade 1 using data collection techniques such as observation, interviews and document analysis. The research results show that efforts to improve student learning outcomes are through the use of TaRL in a process that includes classifying learning needs, learning design, implementation, and student reflection and evaluation.